Pengaruh Remitansi Terhadap Perbedaan Kesejahteraan Rumah Tangga di Indonesia dengan Metode Propensity Score Matching - Amelia Puspita Sari (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2019)
There is a common assumption in the literature and policymakers that migrant remittances have an essential role in improving the welfare of migrant households in the regions of origin. Payments play the same position in economic development as foreign direct investment and other capital flows. This study observes international and internal remittances in Indonesia that are being made to contribute to assessing the impact of payments on household welfare. Using longitudinal data from Indonesia Family Life Survey (IFLS) from 2000 until 2007 on wave 3 and 4, the study will observe the impact of the development of remittance income on the household accumulated asset as a measure of well-being between recipients and non-recipients. This research uses propensity score matching (PSM) method and difference-in-difference (DID) to measure the revenue impact of remittances on household assets and compare them to non-remittance households. It was found that there are significant differences between the well-being of recipients with non-recipient remittances households.